(untitled) (Indo-MathEdu Intellectuals Journal, 2026)
This study aims to map the scientific publication landscape on character education from an Islamic perspective using a Google Scholar–based bibliometric approach. Data were collected through Publish or Perish using the query (“character education” OR “moral education”) AND Islam for the 2015–2025 publication period, exported in RIS format, and analyzed in VOSviewer to generate keyword co-occurrence maps. The dataset consists of 500 documents with 18,309 total citations, averaging 1,664.45 citations per year and 36.62 citations per document. Citation impact indicators show an h-index of 62 and a g-index of 103, and most documents have received at least one citation (488 documents with ≥1 citation). VOSviewer visualizations position “character education” as the most dominant and central node, closely connected to conceptual and implementation-related themes such as “moral education,” “concept,” “school,” “Islamic boarding school/Islamic boarding school,” “management,” “character education program,” “family,” and “child,” while “digital era” emerges as a peripheral contemporary context. Overall, the mapping indicates that research on Islamic character education forms a thematic structure linking conceptual–normative foundations with institutional and programmatic dimensions of implementation. This study contributes a thematic roadmap that can inform more focused future research, particularly by strengthening connections across clusters and exploring still-peripheral topics.